Open and sustainable innovation in the modern context of business-strategy development - Slava, Svetlana Stepanovna; Kalantaridis, Christos; Savchenko, Olga Igorevna; Poberezhyi, Roman Olegovich (Національний технічний університет "Харківський політехнічний інститут", 2021)
It is noted that one of the main factors that complicates the current situation is the quarantine restrictions caused by the Covid-19 pandemic. New conditions require new approaches and understanding of both the organization of the country's international policy and business. Global processes demonstrate a constant growth in the importance of the impact of innovation. The intensification of scientific and technological progress and trends inherent in the current stage of economic development indicate that the type of innovation for enterprises will be decisive, and the economy will become even more innovative. The problem statement is to consider corporate strategies aimed at studying and understanding the sources of types of knowledge for creating and promoting innovations in Ukraine. The article is aimed at researching the current state of open and sustainable innovation, the characteristics of the origin and use of external knowledge, which are key in the innovation process. The article focuses on the consideration of open and sustainable innovation. The modern business environment creates completely different conditions for the creation of innovations in enterprises than those that formed the basis for the formation of an open innovation space. The aim of the article is to study the origin of external knowledge used in the innovation process. Innovative enterprises successfully use the innovation process, despite the negative consequences of the external environment, they need to learn how to adapt to new markets, new rules for organizing their activities, and radical innovators in such conditions require special attention.

Стаття спрямована на дослідження сучасного стану відкритих та стійких інновацій, особливостей походження та використання зовнішніх знань, які є ключовими в інноваційному процесі. У статті особлива роль відводиться розгляду відкритих та стійких інновацій. Сучасне бізнес-середовище формує зовсім інші умови для створення інновацій на підприємствах, ніж ті, які лежали в основі формування відкритого інноваційного простору. Мета статті полягає у вивченні джерел походження зовнішніх знань, які використовуються у інноваційному процесі. Інноваційні підприємства успішно використовують інноваційний процес, незважаючи на негативні наслідки зовнішнього середовища, їм необхідно навчитися пристосовуватися до нових ринків, нових правил організації своєї діяльності та радикальні новатори в таких умовах потребують особливої уваги. Розглянуто емпіричні дослідження в Україні, які показали, що виклики зовнішнього бізнес-середовища не обмежують підприємства в їх інноваційній активності, також наголошується, що в довгостроковій перспективі, без неї неможливий подальший економічний та культурний розвиток.
Відкриті та стійкі інновації у сучасному контексті розвитку бізнес-стратегій
Keywords: open innovation; sustainable innovation; innovative enterprise; development; economic crisis; відкриті інновації; стійкі інновації; інноваційне підприємство; розвиток; економічна криза